PERSEPSI PENDENGAR TENTANG CITRA RRI PRO 1 STASIUN ENDE FLORES SEBAGAI RADIO SIARAN PEDESAAN - Mustika Jima, Maria Mega; Rusmiwari, Sugeng (Jurnal Komunikasi Nusantara, 2019)
The existence of Radio in the midst of the community has a very big role, because it is to meet the needs of the local community. Thus the need for public perception about the image of RRI Ende Flores Pro 1. The purpose of this study is to find out how listeners' perceptions about the image of RRI Pro 1 and the supporting factors of the RRI Pro 1 image of Ende Flores station as a rural broadcast radio. In this study used a qualitative research method with data collection steps carried out through observation, documentation and interviews with informants in the field obtained through sampling. From that step, data analysis is performed using an interactive data analysis model that includes the process of data reduction, data presentation and drawing conclusions. From the research conducted, a conclusion has been reached; (1) Listeners' perceptions about the image of RRI Pro 1 Ende Flores Station as a rural radio broadcast viewed from motivation, attention, cognition, attitude and response. The perception has been built so that the community is greatly helped through rural broadcasts; (2) In building the listener's perception of the image of RRI pro 1 Ende Flores station, the supporting factors are stimulus, informative, time period in listening to rural broadcasts and perception. Which affects the formation of public perception through the program.